Study of the Species Composition of Harmful Organisms in Akunk Educational Research Farm - Manvelyan, A. A.; Ghazaryan, M. H. (ՀԱԱՀ հիմնադրամ)
The article considers the species composition of pests studied in the apple and pear orchards of Akunk Organic Agricultural Experimental Farm in 2020-2021. Twenty four species of harmful organisms have been identified, 17 of which are pests, 1 is a tick and 6 are diseases. Among the harmful organisms the Hoplocampa testudinea and Cydia pomonella were identified on the apple trees, and Fire blight was found on the pear trees.
Keywords: Agronomy and Agroecology